Three-phase reinforced high-strength aluminum alloy and preparation method thereof

By adopting a three-phase strengthening method in aluminum alloy, combined with nanoprecipitation phase, nano-hydroxyapatite rod-shaped particles and modified spherical carbon nanoparticles, the problem that a single filler cannot improve toughness is solved, the strength and toughness is improved, and stable mechanical properties are formed through solid solution treatment.

CN119710374APending Publication Date: 2025-03-28SHANDONG INNOVATION PRECISION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411870736.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the development of high-strength aluminum alloys, the addition of a single filler cannot effectively improve toughness. How to achieve the increase in strength through the interaction between multiple phases and make up for the lack of strength is a technical challenge.

Method used

Three-phase reinforced aluminum alloys are used, including nanoprecipitation phases, nano-hydroxyapatite rod-shaped particles and modified spherical carbon nanoparticles in the aluminum alloy. The three-phase nanoparticles provide the main strength increment through solid solution treatment, making up for the strength loss caused by cell structure display and dislocation recovery.

Benefits of technology

The increase in strength is achieved, the toughness and overall performance of aluminum alloy are improved, and a stable microstructure and adjustable mechanical properties are formed through solid solution treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a three-phase reinforced high-strength aluminum alloy and a preparation method thereof.The preparation method comprises the following steps that Ni powder, Cr powder, Fe powder and Co powder are taken and subjected to hot melting, and an alloy block is obtained; aluminum powder is taken and placed in a vacuum induction melting furnace to be preheated; heating to completely melt the aluminum powder; continuously heating, adding an alloy block, and preserving heat; cooling, adding the nano-hydroxyapatite rod-like particles and the modified spherical carbon nanoparticles, uniformly mixing, preserving heat, and cooling to obtain the aluminum alloy. And the aluminum alloy is subjected to solution treatment, and the aluminum alloy is obtained. Three phases are adopted for strengthening the aluminum alloy, the three phases comprise a nanometer precipitated phase, nanometer hydroxyapatite rod-shaped particles and modified spherical carbon nanoparticles in the aluminum alloy, the nanometer hydroxyapatite rod-shaped particles surround a cellular structure of the nanometer precipitated phase, the modified spherical carbon nanoparticles and an aluminum alloy matrix keep a K-S orientation relation, and after solution treatment, the nanometer precipitated phase and the modified spherical carbon nanoparticles are subjected to heat treatment, so that the strength of the aluminum alloy is improved. When the cell-shaped structure disappears, the three-phase nanoparticles provide main intensity increment, and intensity deficiency caused by cell-shaped structure display and dislocation recovery is made up.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloy materials, and in particular to a three-phase strengthened high-strength aluminum alloy and a preparation method thereof. Background Art

[0002] Aluminum alloy, as a widely used engineering material, has excellent properties such as light weight, high specific strength, and easy recycling. It is particularly important in industries such as shipbuilding, aviation, automobiles, electricity, and construction. In recent decades, aluminum alloys have developed in two directions: one is to develop new high-strength and high-toughness aluminum alloy materials to meet the needs of aviation and aerospace; the other is to develop a series of civilian aluminum alloy materials that can meet various usage conditions. High-strength and high-toughness aluminum alloys mainly include 2××× and 7××× series IM traditional molten aluminum alloys, as well as PM powder metallurgy aluminum alloys, SF injection molding aluminum alloys, aluminum-based composite materials, superplastic aluminum alloys, etc. developed on their basis. In the development of high-strength aluminum alloys, by adding a single filler (reinforcement phase), such as ceramic particles, the strength and hardness can be appropriately improved, but its toughness will be affected. How to achieve strength increment and make up for the lack of strength through the interaction between multiple phases is the problem that this patent needs to solve. Summary of the invention

[0003] Technical problem to be solved: In view of the above technical problems, the purpose of the present invention is to provide a three-phase strengthened high-strength aluminum alloy and a preparation method thereof, which adopts a three-phase strengthened aluminum alloy. The three phases include a nano-precipitated phase in the aluminum alloy, nano-hydroxyapatite rod-shaped particles and modified spherical carbon nanoparticles. The nano-hydroxyapatite rod-shaped particles surround the cellular structure of the nano-precipitated phase, and the modified spherical carbon nanoparticles maintain a KS orientation relationship with the aluminum alloy matrix. After solution treatment, the cellular structure disappears, and the three-phase nanoparticles provide the main strength increment to make up for the strength loss caused by the display of the cellular structure and dislocation recovery.

[0004] Technical solution: A three-phase reinforced high-strength aluminum alloy, comprising the following components, by weight: 100 parts of aluminum alloy matrix powder, 3-7 parts of nano-hydroxyapatite rod-shaped particles, and 2-5 parts of modified spherical carbon nanoparticles. Furthermore, the aluminum alloy matrix powder has a composition of Ni: 2.5-3.8%, Cr: 1.0-2.0%, Fe: 1.0-2.0%, Co: 1.0-2.0%, and the balance is Al. Furthermore, the nano-hydroxyapatite rod-shaped particles have a diameter of 10-20 nm and a length of 30-40 nm. Furthermore, the modified spherical carbon nanoparticles have a particle size of 100-300 nm and a porous surface with a pore size of 3-13 nm. Furthermore, the preparation method of the modified spherical carbon nanoparticles is as follows: Step 1: Add 23 g of sodium metal and 20 mL of 50°C boiling point perfluorocarbon into a reaction vessel. 2 Expel the air from the reaction vessel and seal it; Step 2: Place in a muffle furnace at 400°C for 12 hours; Step 3: Cool to room temperature and wash with ethanol; Step 4: drying in an oven to obtain spherical carbon nanoparticles; Step 5: Take 20g of spherical carbon nanoparticles and disperse them into 500mL of 3-4M potassium hydroxide solution and stir them thoroughly; Step 6: Filter, dry, transfer to a sintering furnace, sinter under a nitrogen atmosphere, and cool naturally to obtain modified spherical carbon nanoparticles. Furthermore, in step 6, the sintering temperature is 800° C. and the holding time is 5 hours. The preparation method of the above three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take Ni powder, Cr powder, Fe powder and Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33Pa, and then preheat it. The preheating temperature is 300-400℃, and the preheating time is 15-25min. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 10-20 kPa, and raise the temperature to 700-800 ° C to completely melt the aluminum powder; S4: Continue to raise the temperature to 1950°C, add the alloy block, and keep warm for 15-20 minutes; S5: cooling to 800-850°C, adding nano-hydroxyapatite rod-shaped particles and modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 3-5 minutes, cooling, and obtaining an aluminum alloy; S6: Perform solid solution treatment on the aluminum alloy to obtain a three-phase strengthened high-strength aluminum alloy. Furthermore, the solution treatment conditions in S6 are as follows: heating the vacuum annealing furnace to 800° C. at a heating rate of 10° C. / min, placing the aluminum alloy, keeping the temperature for 30-40 minutes, and then cooling the alloy to room temperature with the furnace. Beneficial effects: 1. The present invention adopts a three-phase strengthened aluminum alloy, wherein the three phases include a nano-precipitated phase in the aluminum alloy, nano-hydroxyapatite rod-shaped particles and modified spherical carbon nano-particles. The nano-hydroxyapatite rod-shaped particles surround the cellular structure of the nano-precipitated phase, and the modified spherical carbon nano-particles maintain a KS orientation relationship with the aluminum alloy matrix. After solution treatment, the cellular structure disappears, and the three-phase nano-particles provide the main strength increment to make up for the strength loss caused by the display of the cellular structure and dislocation recovery. 2. The present invention adopts modified spherical carbon nanoparticles, which have a porous structure and a large specific surface area. They not only have a strong interface bonding force with the aluminum alloy, but can also significantly refine the primary α-Al dendrites to form a strengthening phase. In addition, they can also form a protective layer on the surface of the aluminum alloy to reduce the intrusion of corrosive media. 3. The present invention adopts solution treatment to achieve controllable strength and elongation at break, forming a strip pillow with a stable microstructure and adjustable mechanical properties. 4. The nano-hydroxyapatite rod-shaped particles in the present invention can be used as a dispersion medium to help improve the dispersibility of the modified spherical carbon nanoparticles in the matrix, thereby improving the overall performance of the aluminum alloy. DETAILED DESCRIPTION The present invention proposes a three-phase strengthened high-strength aluminum alloy and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example 1 The preparation method of modified spherical carbon nanoparticles is as follows: Step 1: Add 23 g of sodium metal and 20 mL of 50°C boiling point perfluorocarbon into a reaction vessel. 2 Expel the air from the reaction vessel and seal it; Step 2: Place in a muffle furnace at 400°C for 12 hours; Step 3: Cool to room temperature and wash with ethanol; Step 4: drying in an oven to obtain spherical carbon nanoparticles; Step 5: Take 20 g of spherical carbon nanoparticles and disperse them into 500 mL of 3 M potassium hydroxide solution and stir them thoroughly; Step 6: Filter, dry, transfer to a sintering furnace, and sinter in a nitrogen atmosphere at a sintering temperature of 800°C for 5 hours. Cool naturally to obtain modified spherical carbon nanoparticles with a particle size of 100-300 nm and a porous surface with a pore size of 3-13 nm. Example 2 The preparation method of modified spherical carbon nanoparticles is as follows: Step 1: Add 23 g of sodium metal and 20 mL of 50°C boiling point perfluorocarbon into a reaction vessel. 2 Expel the air from the reaction vessel and seal it; Step 2: Place in a muffle furnace at 400°C for 12 hours; Step 3: Cool to room temperature and wash with ethanol; Step 4: drying in an oven to obtain spherical carbon nanoparticles; Step 5: Take 20 g of spherical carbon nanoparticles and disperse them into 500 mL of 3.5 M potassium hydroxide solution and stir them thoroughly; Step 6: Filter, dry, transfer to a sintering furnace, and sinter in a nitrogen atmosphere at a sintering temperature of 800°C for 5 hours. Cool naturally to obtain modified spherical carbon nanoparticles with a particle size of 100-300 nm and a porous surface with a pore size of 3-13 nm. Example 3 The preparation method of modified spherical carbon nanoparticles is as follows: Step 1: Add 23 g of sodium metal and 20 mL of 50°C boiling point perfluorocarbon into a reaction vessel. 2 Expel the air from the reaction vessel and seal it; Step 2: Place in a muffle furnace at 400°C for 12 hours; Step 3: Cool to room temperature and wash with ethanol; Step 4: drying in an oven to obtain spherical carbon nanoparticles; Step 5: Take 20 g of spherical carbon nanoparticles and disperse them into 500 mL of 4 M potassium hydroxide solution and stir them thoroughly; Step 6: Filter, dry, transfer to a sintering furnace, and sinter in a nitrogen atmosphere at a sintering temperature of 800°C for 5 hours. Cool naturally to obtain modified spherical carbon nanoparticles with a particle size of 100-300 nm and a porous surface with a pore size of 3-13 nm. The specific surface area of ​​the modified spherical carbon nanoparticles was measured, and the results are shown in Table 1 below: Table 1 <![CDATA[Specific surface area (m 2 / g)]]> Example 1 2674 Example 2 2701 Example 3 2730 The modified spherical carbon nanoparticles prepared in Example 3 were selected for subsequent experiments. Example 4 A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 15 minutes; S5: cooling to 850°C, adding 5 parts of nano-hydroxyapatite rod-shaped particles with a diameter of 10-20 nm and a length of 30-40 nm and 4 parts of modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 5 minutes, cooling, and obtaining an aluminum alloy; S6: performing solid solution treatment on the aluminum alloy. The solid solution treatment conditions are as follows: heating the vacuum annealing furnace to 800°C at a heating rate of 10°C / min, placing the aluminum alloy, keeping the temperature for 35 minutes, and then cooling to room temperature with the furnace to obtain a three-phase strengthened high-strength aluminum alloy. Example 5 A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 20 minutes; S5: cooling to 850°C, adding 5 parts of nano-hydroxyapatite rod-shaped particles with a diameter of 10-20 nm and a length of 30-40 nm and 4 parts of modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 5 minutes, cooling, and obtaining an aluminum alloy; S6: performing solid solution treatment on the aluminum alloy. The solid solution treatment conditions are as follows: heating the vacuum annealing furnace to 800°C at a heating rate of 10°C / min, placing the aluminum alloy, keeping the temperature for 35 minutes, and then cooling to room temperature with the furnace to obtain a three-phase strengthened high-strength aluminum alloy. Example 6 A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 20 minutes; S5: cooling to 850°C, adding 3 parts of nano-hydroxyapatite rod-shaped particles with a diameter of 10-20 nm and a length of 30-40 nm and 4 parts of modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 5 minutes, cooling, and obtaining an aluminum alloy; S6: performing solid solution treatment on the aluminum alloy. The solid solution treatment conditions are as follows: heating the vacuum annealing furnace to 800°C at a heating rate of 10°C / min, placing the aluminum alloy, keeping the temperature for 35 minutes, and then cooling to room temperature with the furnace to obtain a three-phase strengthened high-strength aluminum alloy. Example 7 A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 20 minutes; S5: cooling to 850°C, adding 7 parts of nano-hydroxyapatite rod-shaped particles with a diameter of 10-20 nm and a length of 30-40 nm and 4 parts of modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 5 minutes, cooling, and obtaining an aluminum alloy; S6: performing solid solution treatment on the aluminum alloy. The solid solution treatment conditions are as follows: heating the vacuum annealing furnace to 800°C at a heating rate of 10°C / min, placing the aluminum alloy, keeping the temperature for 35 minutes, and then cooling to room temperature with the furnace to obtain a three-phase strengthened high-strength aluminum alloy. Example 8 A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 20 minutes; S5: cooling to 850°C, adding 5 parts of nano-hydroxyapatite rod-shaped particles with a diameter of 10-20 nm and a length of 30-40 nm and 2 parts of modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 5 minutes, cooling, and obtaining an aluminum alloy; S6: performing solid solution treatment on the aluminum alloy. The solid solution treatment conditions are as follows: heating the vacuum annealing furnace to 800°C at a heating rate of 10°C / min, placing the aluminum alloy, keeping the temperature for 35 minutes, and then cooling to room temperature with the furnace to obtain a three-phase strengthened high-strength aluminum alloy. Example 9 A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 20 minutes; S5: cooling to 850°C, adding 5 parts of nano-hydroxyapatite rod-shaped particles with a diameter of 10-20 nm and a length of 30-40 nm and 5 parts of modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 5 minutes, cooling, and obtaining an aluminum alloy; S6: performing solid solution treatment on the aluminum alloy. The solid solution treatment conditions are as follows: heating the vacuum annealing furnace to 800°C at a heating rate of 10°C / min, placing the aluminum alloy, keeping the temperature for 35 minutes, and then cooling to room temperature with the furnace to obtain a three-phase strengthened high-strength aluminum alloy. Example 10 A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 20 minutes; S5: cooling to 850°C, adding 5 parts of nano-hydroxyapatite rod-shaped particles with a diameter of 10-20 nm and a length of 30-40 nm and 4 parts of modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 5 minutes, cooling, and obtaining an aluminum alloy; S6: performing a solution treatment on the aluminum alloy. The solution treatment conditions are as follows: heating the vacuum annealing furnace to 800°C at a heating rate of 10°C / min, placing the aluminum alloy, keeping the temperature for 30 minutes, and then cooling the alloy to room temperature with the furnace to obtain a three-phase strengthened high-strength aluminum alloy. Embodiment 11 A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 20 minutes; S5: cooling to 850°C, adding 5 parts of nano-hydroxyapatite rod-shaped particles with a diameter of 10-20 nm and a length of 30-40 nm and 4 parts of modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 5 minutes, cooling, and obtaining an aluminum alloy; S6: performing a solution treatment on the aluminum alloy. The solution treatment conditions are as follows: heating the vacuum annealing furnace to 800°C at a heating rate of 10°C / min, placing the aluminum alloy, keeping the temperature for 40 minutes, and then cooling the alloy to room temperature with the furnace to obtain a three-phase strengthened high-strength aluminum alloy. Comparative Example 1 The difference between this embodiment and embodiment 5 is that nano-hydroxyapatite rod-shaped particles are not added. Specifically: A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 20 minutes; S5: cooling to 850°C, adding 4 parts of modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 5 minutes, cooling down, and obtaining an aluminum alloy; S6: performing solid solution treatment on the aluminum alloy. The solid solution treatment conditions are as follows: heating the vacuum annealing furnace to 800°C at a heating rate of 10°C / min, placing the aluminum alloy, keeping the temperature for 35 minutes, and then cooling to room temperature with the furnace to obtain a three-phase strengthened high-strength aluminum alloy. Comparative Example 2 The difference between this embodiment and embodiment 5 is that no modified spherical carbon nanoparticles are added. Specifically: A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 20 minutes; S5: cooling to 850°C, adding 5 parts of nano-hydroxyapatite rod-shaped particles with a diameter of 10-20 nm and a length of 30-40 nm, mixing evenly, keeping the temperature for 5 minutes, cooling, and obtaining an aluminum alloy; S6: performing solid solution treatment on the aluminum alloy. The solid solution treatment conditions are as follows: heating the vacuum annealing furnace to 800°C at a heating rate of 10°C / min, placing the aluminum alloy, keeping the temperature for 35 minutes, and then cooling to room temperature with the furnace to obtain a three-phase strengthened high-strength aluminum alloy. Comparative Example 3 The difference between this embodiment and embodiment 5 is that no solution treatment is performed. Specifically: A method for preparing a three-phase strengthened high-strength aluminum alloy comprises the following steps: S1: Take 3.5 parts of Ni powder, 1.5 parts of Cr powder, 1.5 parts of Fe powder and 1.5 parts of Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take 92 parts of aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33 Pa, and then preheat it. The preheating temperature is 400°C and the preheating time is 20 minutes. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 15kPa, and heat to 700℃ to completely melt the aluminum powder; S4: Continue to heat to 1950℃, add alloy blocks, and keep warm for 20 minutes; S5: Cooling to 850°C, adding 5 parts of nano-hydroxyapatite rod-shaped particles with a diameter of 10-20 nm and a length of 30-40 nm and 4 parts of modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 5 minutes, cooling down, and obtaining an aluminum alloy. The mechanical properties of each embodiment were tested according to the national standard method, and the results are shown in Table 2 below: Table 2

Claims

1. A three-phase strengthened high-strength aluminum alloy, characterized in that: The invention comprises the following components in parts by weight: 100 parts of aluminum alloy matrix powder, 3-7 parts of nano-hydroxyapatite rod-shaped particles, and 2-5 parts of modified spherical carbon nano-particles.

2. A three-phase strengthened high-strength aluminum alloy according to claim 1, characterized in that: The aluminum alloy matrix powder comprises: Ni: 2.5-3.8%, Cr: 1.0-2.0%, Fe: 1.0-2.0%, Co: 1.0-2.0%, and the balance is Al.

3. The three-phase strengthened high-strength aluminum alloy according to claim 1, characterized in that: The nano-hydroxyapatite rod-shaped particles have a diameter of 10-20 nm and a length of 30-40 nm.

4. The three-phase strengthened high-strength aluminum alloy according to claim 1, characterized in that: The modified spherical carbon nanoparticles have a particle size of 100-300 nm and a porous surface with a pore size of 3-13 nm.

5. The three-phase strengthened high-strength aluminum alloy according to claim 1, characterized in that: The preparation method of the modified spherical carbon nanoparticles is as follows: Step 1: Add 23 g of sodium metal and 20 mL of perfluorocarbon with a boiling point of 50°C into a reaction vessel, remove the air in the reaction vessel with N2, and seal it; Step 2: Place in a muffle furnace at 400°C for 12 hours; Step 3: Cool to room temperature and wash with ethanol; Step 4: drying in an oven to obtain spherical carbon nanoparticles; Step 5: Take 20g of spherical carbon nanoparticles and disperse them into 500mL of 3-4M potassium hydroxide solution and stir them thoroughly; Step 6: Filter, dry, transfer to a sintering furnace, sinter under a nitrogen atmosphere, and cool naturally to obtain modified spherical carbon nanoparticles.

6. The three-phase strengthened high-strength aluminum alloy according to claim 1, characterized in that: In step 6, the sintering temperature is 800° C. and the holding time is 5 hours.

7. A method for preparing a three-phase strengthened high-strength aluminum alloy, characterized in that: The following steps are involved: S1: Take Ni powder, Cr powder, Fe powder and Co powder, melt them by arc melting and high frequency heating under Ar atmosphere protection, stir and melt them evenly to obtain an alloy block; S2: Take aluminum powder, place it in a vacuum induction melting furnace, evacuate it to below 1.33Pa, and then preheat it. The preheating temperature is 300-400℃, and the preheating time is 15-25min. S3: Close the vacuum system, fill with high-purity Ar to make the relative pressure 10-20 kPa, and raise the temperature to 700-800 ° C to completely melt the aluminum powder; S4: Continue to raise the temperature to 1950°C, add the alloy block, and keep warm for 15-20 minutes; S5: cooling to 800-850°C, adding nano-hydroxyapatite rod-shaped particles and modified spherical carbon nanoparticles, mixing evenly, keeping the temperature for 3-5 minutes, cooling, and obtaining an aluminum alloy; S6: Perform solid solution treatment on the aluminum alloy to obtain a three-phase strengthened high-strength aluminum alloy.

8. The method for preparing a three-phase strengthened high-strength aluminum alloy according to claim 7, characterized in that: The solution treatment conditions in S6 are as follows: heating the vacuum annealing furnace to 800° C. at a heating rate of 10° C. / min, placing the aluminum alloy, keeping the temperature for 30-40 minutes, and then cooling to room temperature with the furnace.